Revisiting Angular Momentum Quantization in Bohr's Atomic Model - Jorge Henrique de Oliveira Sales; Alfredo Takashi Suzuki (The Journal of Engineering and Exact Sciences)
One of the most important developments of modern science was the emergence of the concept of energy quantization which forced its way into our previous classical understanding of matter in nature. Modern day view of matter constituents and present understanding of atomic structure basic to quantum chemistry arose in those first decades of last century. In this line, a key feature for the understanding of microscopic atomic structures and their stability was the concept of angular momentum quantization. To capture the beauty and the power of these concepts is therefore extremely relevant for apprehending the contemporary view of matter, energy and interactions in nature. In this work we present a possible alternative approach of quantizing the atomic orbit for the hydrogen's atom model proposed by Bohr without using his hypothesis of angular momentum quantization from the start. In our approach here we show that when we identify the number of photons and the quantum number for the orbit, we are led to Bohr's hypothesis as a consequence of the Planck's energy quantization.